2010
DOI: 10.1144/sp335.26
|View full text |Cite
|
Sign up to set email alerts
|

Deformation temperatures, vorticity of flow and strain symmetry in the Loch Eriboll mylonites, NW Scotland: implications for the kinematic and structural evolution of the northernmost Moine Thrust zone

Abstract: The Moine Thrust zone (MTZ) marks the Caledonian foreland-to-hinterland transition zone at the base of the Scandian (c. 430 Ma) orogenic wedge. In the Loch Eriboll region, the upper ductile part of the MTZ is composed in ascending order of two regionally extensive thrust sheets (Upper Arnaboll-Creag na Faoilin and Creagan) and is overlain by the Moine Nappe. Quartz crystal fabrics, kinematic vorticity (Wm), and strain estimates from the ductile thrust sheets in this region are used to determine how pure and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 98 publications
0
40
1
Order By: Relevance
“…It is now known that these zones form boundaries between the major sub-divisions of the Moine (see Fig. 1 and Thigpen et al 2010).…”
Section: Differentiating Mylonites From Schists or Where Do The Moinementioning
confidence: 99%
See 2 more Smart Citations
“…It is now known that these zones form boundaries between the major sub-divisions of the Moine (see Fig. 1 and Thigpen et al 2010).…”
Section: Differentiating Mylonites From Schists or Where Do The Moinementioning
confidence: 99%
“…Murchison went on to refute Nicol's interpretation strongly in a footnote in his 1858 paper (Murchison 1858b) and continued this refutation in three papers published both before (Murchison 1859) and after (Murchison & Geikie 1861a, b) the publication of Nicol's 1860 paper. (Supplied by Ryan Thigpen, based on Krabbendam et al 2008, also see Thigpen et al 2010. ) Nicol (1860) concluded that 'the line of junction, where this conformable succession is said to occur, is clearly a line of fault, everywhere indicated by proofs of fracture, contortion of the strata, and powerful igneous action'.…”
Section: Geological Observations Leading To the Highland Controversymentioning
confidence: 99%
See 1 more Smart Citation
“…Work has previously focussed on aluminium in quartz [Dennen et al, 1970;Götze et al, 2001], 'fractal' geometry [Kruhl and Nega, 1996;Mamtani and Greiling, 2010;Wu et al, 2006], thermoluminescence [Sawakuchi et al, 2011], caxis opening angles [e.g. Thigpen et al, 2010] and importantly for this study, titanium in quartz [Wark and Watson, 2006] to give quartz crystallisation temperatures, with variable success.…”
Section: ) Introductionmentioning
confidence: 99%
“…1) date around 600 Ma and have been linked to late Neoproterozoic rifting of Rodinia (Kinny et al 2003b;Oliver et al 2008). Metamorphic grade in the Morar Group reached middle amphibolite-facies grade (Fettes et al 1985;Thigpen et al 2010): kyanite has overgrown andalusite in the thermal aureole of the Carn Chuinneag granite (Tilley 1935, Wilson & Shepherd 1979, attesting to at least medium-high pressures during Caledonian orogenesis.…”
Section: Geological Settingmentioning
confidence: 99%